Bimtek Gerakan Indonesia Membaca (GIM) untuk Guru Pendidikan Dasar Kabupaten Deli Serdang - Kisno Kisno; Calen Calen; Mega Romauly Tampubolon; Arni Mulati; Eka Pratiwi Septania Parapat; Yuanita Tri Sapdani; Wardatul Hasanah; Victor Marudut Mulia Siregar; Sarida Sirait (Universitas Mathla'ul Anwar Banten, 2021)
INDONESIA READING MOVEMENT TECHNICAL GUIDANCE FOR PRIMARY SCHOOL TEACHERS IN DELI SERDANG REGENCY. Since 2015, the government of Indonesia has accelerated Indonesia Literacy Movement. However the effectiveness of this program wasnot reflected in the results of students’ PISA test result in 2018. In attempt to the improvement of this program, the volunteers decided to carry out a technical guidance to increase the reading literacy of primary school teachers in Deli Serdang Regency, North Sumatera. This voluntarily activity aimed to share the knowledge and best practice of fun and interactive reading. 40 primary school teachers from two state schools were involved in this community service program. İn the beginning, they had to complete the pre-test. Then, they were given a workshop about how to perform fun reading and created their own best practice. The result of their work were presented in front of the other groups and at last they completed the post-test. As the result of this activity, there was a significant increase on the teachers’ knowledge about fun reading and Indonesia Reading Movement based on the pre-test and post-test. İn addition, the teachers were able to produce their own fun reading activities based on their interests through Uniterrupted Sustained Silent Reading (USSR) Journal and Reading Pyramid.